Peran Museum Deli Serdang sebagai Sarana Literasi Budaya di Lubuk Pakam - Muhammad Rizki; Yusra Dewi Siregar (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The richness and diversity of the nation's culture can be a source of forging a common identity (nationalism), but it can also be a breeding ground for social insecurity and conflict. Through ethnic and cultural diversity, identity politics, globalization and regional autonomy all contribute to social tensions. Therefore, efforts should be made to understand the potential for cultural heritage in the form of museums in order to boost nationalism and the function of museums. The aim of this research is to better understand the potential of museums as a tool for increasing cultural literacy and thus nationalism. This study uses a descriptive qualitative approach, which is defined as research that tries to collect data subjectively through observation and interviews, with outcomes explained using descriptions. The results of the study show that the distribution of the Deli Serdang Lubuk Pakam museums shows that the potential for the museum is quite large when viewed in terms of collections, display plans, and the number of visitors. The majority of museum visitors consist of students; Therefore, it is important for collection materials to promote cultural literacy so that visitors can develop a stronger sense of national pride. There are several challenges to be faced when trying to promote cultural literacy through museums, including internal and external constraints. As a result, in order to maximize the role played by museums, it is necessary for the central and regional governments to make increased efforts towards implementing unique programs, such as mandatory museum visits